Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae) - Guerrero, Roberto J. (Zootaxa, 2021)
Some species of the ant genus Forelius can be misclassified as the genus Tapinoma due to the convergent reduction of the petiolar scale. I review the taxonomic status of Tapinoma antarcticum Forel 1904 and Tapinoma heyeri Forel 1902. Morphological evidence supports the transfer of these names to the ant genus Forelius. Proposed taxonomic changes are as follows: Forelius antarcticus (Forel) comb. nov. (=Forelius fazi (Santschi 1923) comb. nov., =Forelius eidmanni Goetsch 1933 comb. rev.); Forelius heyeri (Forel) comb. nov. (=Forelius heyeri risii (Forel 1912) comb. and syn. nov., =Forelius pusillus (Santschi 1922) syn. nov., =Forelius tucumanus (Kusnezov 1953) syn. nov.). Lectotypes for Forelius antarcticus and Forelius heyeri are designated. The worker of Forelius heyeri, as well as the worker and queen of Forelius antarcticus are diagnosed and redescribed. Multifocus images for lectotype workers are provided. Morphological variation within and between species of Forelius with rounded spiracles is discussed.